Induction of Tyrosine Phosphorylation of UV-Activated EGFR by the Beta-Human Papillomavirus Type 8 E6 Leads to Papillomatosis - Taute, Stefanie; Pfister, Herbert J.; Steger, Gertrud (Frontiers in Microbiology, 2017)
Epidemiological evidence is accumulating that beta human papillomaviruses (HPV) synergize with UV-light in the development of precancerous actinic keratosis, and cutaneous squamous cell carcinomas (cSCC), one of the most common cancers in the Caucasian population. We previously demonstrated the tumorigenic activity of beta HPV type 8 (HPV8) in the skin of transgenic mice and its cooperation with UV-light. Analysis of underlying mechanisms now showed that in keratinocytes expressing the HPV8E6 protein a transient increase of tyrosine phosphorylated epidermal growth factor receptor (EGFR) in response to UV-irradiation occurred, while EGFR tyrosine phosphorylation i.e. receptor tyrosine kinase (RTK)-activity was hardly affected in empty vector control cells. FACS and immunofluorescences revealed that the EGFR was internalized into early endosomes in response to UV-exposure in both, HPV8E6 positive and in control cells, yet with a higher rate in the presence of HPV8E6. Moreover, only in HPV8E6 expressing keratinocytes the EGFR was further sorted into CD63+ intraluminal vesicles, indicative for trafficking to late endosomes. The latter requires the ubiquitination of the EGFR, and in correlation, we could show that only in HPV8E6 positive keratinocytes the EGFR was ubiquitinated upon UV-exposure. HPV8E6 and tyrosine phosphorylated EGFR directly interacted which was enhanced by UV-irradiation. The treatment of K14-HPV8E6 transgenic mice with Canertinib, an inhibitor of the RTK-activity of the EGFR, suppressed skin papilloma growth in response to UV-irradiation. This confirms the crucial role of the RTK-activity of the EGFR in HPV8E6 and UV-mediated papillomatosis in transgenic mice. Taken together, our results demonstrate that HPV8E6- alters the signaling of the UV-activated EGFR and this is a critical step in papilloma formation in response to UV-light in transgenic mice. Our results provide a molecular basis how a beta-HPV type may support early steps of skin tumor formation in cooperation with UV-light.